How does perceived risk mediate associations between perceived safety and parental restriction of adolescents' physical activity in their neighborhood? - Carver Alison; Timperio Anna; Hesketh Kylie; Crawford David (BMC, 2012)
Abstract Background There is evidence that adolescence is a critical period of decline in physical activity. However, adolescents may have limited opportunities to be physically active outdoors if their parents are concerned about neighborhood safety and restrict their adolescent's physical activity within their neighborhood. Pathways that lead to parental restriction of adolescents' physical activity (constrained behavior) are under-researched. This study aimed to examine perceived risk as a potential mediator of associations between perceived safety/victimization and constrained behavior. Methods Cross-sectional study of adolescents (43% boys) aged 15-17 years (n = 270) in Melbourne, Australia. Parents reported perceived safety (road safety, incivilities and personal safety) and prior victimization in their neighborhood, perceived risk of their children being harmed and whether they constrained their adolescent's physical activity. Constrained behavior was categorized as 'avoidance' or 'defensive' behavior depending on a whether physical activity was avoided or modified, respectively, due to perceived risk. MacKinnon's product-of-coefficients test of mediation was used to assess potential mediating pathways between perceived safety/victimization and constrained behavior. Results For girls only, perceived risk was a significant mediator of associations between perceived road safety and avoidance/defensive behavior, and between perceived incivilities, perceived personal safety, victimization and defensive behavior. Conclusions Associations between perceived safety/victimization and constrained behavior are complex. Findings may guide the design of interventions that aim to improve actual and perceived levels of safety and reduce perceptions of risk. This is of particular importance for adolescent girls among whom low and declining levels of physical activity have been observed worldwide.